Urgent-Start Peritoneal Dialysis – a viable option? A case report and literature review - Tavares, J (2020)
Background: Many patients with end -stage renal disease start renal replacement therapy in an unplanned manner. The vast majority initiate hemodialysis by a central venous catheter, since its use is more widespread and available. This technique is associated with a high risk of infection and damage of the vascular patrimony associated with the use of central veins. Urgent -start peritoneal dialysis comes as an alternative treatment for selected patients. Case report: A 55 -year -old woman with focal segmental glomerulosclerosis presented with a rapid decline of renal function and was given renal replacement therapy counselling and opted for peritoneal dialysis. Her chosen modality was postponed for one month due to early uremic symptoms, followed by hemodialysis start through a central venous catheter. During this period a sepsis due to central venous catheter infection occurred, implying four weeks of intravenous antibiotics. Discussion and Conclusion: Although there has been an increase in the number of publications on urgent -start peritoneal dialysis, showing that this technique has comparable results either to urgent -start hemodialysis and planned -start peritoneal dialysis, there still is some resistance to the use of this modality. Given the importance of this subject, this review aims to describe and summarize the available evidence on urgent -start peritoneal dialysis outcomes. Moreover, specific barriers are addressed. Its use is encouraged in hospitals where peritoneal dialysis is available, as an opportunity to improve chronic kidney disease patient management and transition to dialysis.